Hubungan Sanitasi Lingkungan, Perilaku Pengendalian Jentik dan Nyamuk, dan Kepadatan Penduduk dengan Penyakit Demam Berdarah Dengue (DBD) di Kabupaten Jember (Relationship of Environmental Sanitation, Mosquito and Larva Control Behavior, and Population De - Mochammad Sholehhudin; Isa Ma’rufi; Ellyke Ellyke (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Dengue Haemorhagic Fever (DHF) is a public health problem in Indonesia which has the number of sufferers always be increase and spread more widely. East Java is one dengue endemic areas. One of the districts in East Java that dengue endemic is Jember. The number of dengue cases continued to increase from year 2008 to 2012. In 2010 an outbreak (KLB) with the number of case is 1.494 and the incident rate is 62 per 100.000 poppulation. This study aim to describe environmental sanitation, mosquito and larva control (PJN) behavior, and population density. Beside there to analyze the relationship between environmental sanitation, mosquito and larvae control behavior, and population density with dengue haemorhagic fever in Jember. The Method is observational research use a cross sectional design. Test analysis use the association of asymmetry lambda and association somers’d. The results and conclution of the study showed the environmental sanitation and PJN behavior in the middle category. Based on statistic test showed that there was no significant relationship between environmental sanitation (ñ=0,483), mosquito and larva control behavior (ñ=0,157), and population density (ñ=0,500) with DHF incidence in Jember. Keywords: DHF, Environmental Sanitation, Mosquito Control, Population Density.